LOCAL-MODULAR TECHNOLOGY OF ORGANIZING INDEPENDENT WORK TO DEVELOP STUDENTSʼ ENTREPRENEURIAL SKILLS (Scientific journal of the Fergana State University, 2023)
The main purpose of independent work in the continuing education system, especially in HEIs, is to form and develop the knowledge, skills and abilities necessary for the student to independently complete certain educational materials under the guidance and supervision of a facilitator-teacher. Some views and solutions on this topic are expressed in the article.